Barriers to modern contraceptive practices among selected married women in a Public University in Malaysia. - Najafi, Fatemeh S. A.; Abdul Rahman, Hejar; Juni, Muhamad Hanafiah (Canadian Center of Science and Education, 2011)
In Malaysia, only 30% of the married women use modern contraceptive methods. Low usage of contraceptive methods, results in high rates of unwanted pregnancies and its consequence which includes; psychological problems physical health and unsafe abortion. The main purpose of this study is to understand the barriers of modern contraceptive practices among women in University Putra Malaysia. This study was carried out through two main research questions: 1.What is the women’s perceptions of modern contraceptive methods? 2. Why women do not use modern contraceptive methods? A qualitative research method was used for exploring misconceptions and barriers to contraceptive use among married female staff in University Putra Malaysia (UPM). The data was collected using the non probability, purposive sampling method, from 6 women by face to face interviews, which was also audio-recorded. The records were then transcribed verbatim and analyzed consecutively. This study finding showed there were personal, cultural, and health system barriers to modern contraceptive use. The women have been surrounded by fears, and misconceptions which serve as obstacles to initiation and continuation of contraceptive use. Strong socio-cultural norms and health services barriers including negative response of service providers, and low male family planning activities influence contraceptive use negatively. This study suggests that the promotion of modern contraceptive methods should be considered in women and men educational programs. Further studies should examine health providers’ views and quality of family planning services.